Reproductive traits of the freshwater oyster Etheria elliptica (Bivalvia: Etheriidae) in the Pendjari River, Benin: implications for conservation - AKELE, David; MONTCHOWUI, HOUNNON ELIE; LALEYE, PHILIPPE A. (My University, 2017)
The African freshwater oyster Etheria elliptica, which is of great economic importance throughout the continent, is facing overharvesting in many fisheries in West Africa. Its reproductive traits (sex ratio, size at sexual maturity, oocyte diameter and fecundity) were studied at four stations located along the Pendjari River, northern Benin, in April 2013. Histological techniques were implemented to identify sex and gonad development stages. Oocyte sizes were measured based on the histological images and mean oocyte diameter was 38 µm. Fecundity, estimated by counting the developing eggs, averaged 106 724 eggs and increased significantly with shell size. The average sex ratio was approximately 1:1. Hermaphrodites were rare. Males reached sexual maturity at 57.6 mm dorsoventral height, earlier than females at 64.7 mm. The majority of the oyster specimens were in ripe-spawning stages, indicating that reproductive activities partly took place towards the end of the dry season. Both mature and immature individuals were subjected to harvesting at all the investigated fishing sites. The mean size of exploited oysters was 60.6 mm, lower than the size of females at maturity. Management strategies must enforce the minimum size of 65 mm required for harvesting, particularly in open access sites where juveniles are mostly harvested.
Keywords: fecundity; oocyte diameter; reproductive biology; size-at-maturity